Design of Web-Based Customer Savings Data Information System at Sumber Rejeki Jaya Abadi Cooperative Klaten: Perancangan Sistem Informasi Data Tabungan Nasabah Berbasis Web Di Koperasi Sumber Rejeki Jaya Abadi Klaten - Hidayah, Nurul; Naury, Chairullah; Purbiyanto, Eko (Politeknik Harapan Bangsa Surakarta, 2024)
Koperasi Sumber Rejeki Jaya Abadi is a business entity engaged in financial savings and loans in Klaten Regency. Customers in the cooperative are required to have savings and before applying for loans, they must conduct deposit transactions and maintain a savings account.The cooperative faces issues with manual recording of customer savings transactions, where data is recorded using physical books. This manual process leads to inconsistent data and inefficiency in managing customer savings transactions since data must be accessed one book at a time. Additionally, the use of physical books for reporting transactions means that the reporting process lacks organization. To address these challenges, the author utilizes the System Development Life Cycle (SDLC) methodology in developing the information system. The system is being built using the PHP programming language with the Laravel framework and utilizes the MySQL database. The primary objective of this research is to create an information system that can assist the administration department in managing customer savings at Koperasi Sumber Rejeki Jaya Abadi in Klaten. By implementing the new system, the cooperative aims to improve data consistency and the efficiency of customer savings transactions, eliminating the need to search through physical books, and enhancing the overall reporting process.